The impact of academic research: on character formation, ethical education, and the communication of values in late modern pluralistic societies - Schweiker, William; Welker, Michael; Witte, John; Pickard, Stephen K. (Evangelische Verlagsanstalt, 2021)
"This volume addresses whether, how, and where academic research has an impact on ethical education, character formation, and the communication of values in late modern pluralistic societies. It reflects the great impacts of a global network of research universities, with the enormous range from the natural sciences to mathematics, historical and theological investigations. It offers praises of the institutionalized impact of the search for truth and the defense of tested truth-claims, but also skeptical voices with respect to the ethical impact of academic research today."